ANALISIS TINGKAT KEPUASAN PENGGUNA LAYANAN TRANSMETRO PEKANBARU DENGAN MENGGUNAKAN METODE SERVQUAL - Roy Candra; Leo Sentosa; Gunawan Wibisono (LPPM Universitas Abdurrab, 2025)
Transmetro Pekanbaru is one of the road-based mass transportation services operating in Pekanbaru City, Riau Province. First operating on June 18, 2009, with the number of vehicles operated as many as 20 units serving 2 corridors, namely corridor 01 with the Ramayana - Pandau route. PP and corridor 02 with the Bandar Raya Payung Sekaki Terminal (BRPS) - Kulim.PP route. Until now, Transmetro Pekanbaru serves 8 active corridors with the number of vehicles operating as many as 38 units. This study was conducted to determine the level of satisfaction of Transmetro Pekanbaru users, especially on Routes/Corridors 01 and 02. The analysis method used is the Service Quality method (SERVQUAL), which is a function index of the difference between user expectations and perceptions of a series of satisfaction level factors. The number of samples used was 165 respondents surveyed on both routes. The indicators used for measurement include: Punctuality, crew ability, security, vehicle condition, schedule and route information, fares, and infrastructure (bus stops). Based on the results of the study, the level of service provided by Transmetro Pekanbaru has not been able to satisfy the user community. __________________________________________________________